Developments in Applied Spectroscopy 1963
DOI: 10.1007/978-1-4684-8685-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Infrared Spectra of the Dicyanamide Ion

Abstract: The dicyanamide or dicyanimide ion (NsaC-N-C=N)-is isoelectronic with carbon suboxide and therefore might exist + in a linear resonance form (N-=C=N=C=N-) having the same double bond array as the latter. A comparison of the infrared with Raman spectra should show at once whether this ion is linear or bent, since the linear form would have a center of symmetry and there would therefore be no coincidence in absorption between the two types of spectra.The IR spectrum of this ion has been investigated at the Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Reckeweg et al reported this mode at 682 cm −1 , whereas Perkins observed this mode at 671 cm −1 for the Na salt. 21,40 We tentatively assign the ν 4 symmetric bending mode at 227 cm −1 on the basis of comparison of Raman intensity with our calculations. However, two additional bands are observed at 206 and 240 cm −1 , and calculations reveal that they both have character similar to that of ν 4 (symmetric bending).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Reckeweg et al reported this mode at 682 cm −1 , whereas Perkins observed this mode at 671 cm −1 for the Na salt. 21,40 We tentatively assign the ν 4 symmetric bending mode at 227 cm −1 on the basis of comparison of Raman intensity with our calculations. However, two additional bands are observed at 206 and 240 cm −1 , and calculations reveal that they both have character similar to that of ν 4 (symmetric bending).…”
Section: Resultsmentioning
confidence: 74%
“…The CN symmetric stretching mode (ν 2 ) was observed in the IR and the Raman at 944 and 943 cm −1 , respectively, and is in general agreement with our calculations and the previous study by Reckeweg et al 21 For the Na salt, the CN symmetric stretch was observed at 937 cm −1 (Raman) and 931 cm −1 (IR). 40 The CN asymmetric stretch (ν 8 ) was observed in the IR at 1346 cm −1 , but not observed in the Raman where it could possibly be obscured by the strong T 2g diamond phonon near 1333 cm −1 . The calculated frequency of the CN asymmetric stretching mode at 1422 cm −1 is significantly shifted from the observed position and the origin of this discrepancy is presently unclear.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, several of the 18 post-transition elements have well-established binary cyanides, and the present work is concerned with the characterization of a complex cyanide of iodine, the dicyanoiodate ion [I(CN)J, which is derived from the binary cyanide, iodine cyanide, ICN. Apart from the dicyanamide ion [N(CN)2]-already referred to, the only other dicyano complex ions known are those of the transition metals, Cu(I), Ag (1) and Au (1). The [Ag(CN)J and [Au(CN)~]-ions are known to be linear in their solid potassium salt^,^" but unexpectedly the [Cu(CN)J ion is bent and three-coordinate in its solid potassium salt.…”
Section: Introductionmentioning
confidence: 99%